Evaluation of Bronchoscopy and Bronchoalveolar Lavage Findings in Cats With Aelurostrongylus abstrusus in Comparison to Cats With Feline Bronchial Disease - Crisi, Paolo E.; Johnson, Lynelle R.; Di Cesare, Angela; De Santis, Francesca; Di Tommaso, Morena; Morelli, Simone; Pantaleo, Stefania; Luciani, Alessia; Schaper, Roland; Pampurini, Fabrizio; Boari, Andrea (Frontiers in Veterinary Science, 2019)
The cat lungworm Aelurostrongylus abstrusus is a cause of lower respiratory tract disease worldwide. Bronchoscopy and bronchoalveolar lavage (BAL) are important tools for diagnosing respiratory diseases in cats. Therefore, the aim of the study was to investigate the usefulness of bronchoscopy and BAL in the diagnosis of A. abstrusus. Findings from bronchoscopic examination and BAL of 24 naturally infected cats were evaluated and compared with those of 12 cats with idiopathic Feline Bronchial Diseases (FBDs). Data were analyzed using Mann-Whitney or Fisher's exact tests. No significant bronchoscopic differences were detected between cats with aelurostrongylosis and FBDs in bronchial mucus, nodular lesions and airway collapse. On the other hand, airway hyperemia, epithelial irregularities, and bronchial stenosis were observed more frequently in cats affected by FBDs than aelurostrongylosis, while bronchiectasis was found only in cats infected by A. abstrusus. Neutrophilic, eosinophilic, lymphocytic and mixed inflammation were recorded in both groups. Bacteria or bacterial DNA was identified regardless of the presence or absence of A. abstrusus with no significant differences between groups. Larvae of A. abstrusus were cytologically detected in 5 of the 24 cats (20.8%) with aelurostrongylosis. These results indicate that some findings on bronchoscopic examination can be described more frequently in cats infected by A. abstrusus than in animals with other diseases, though bronchial alterations and cytological findings in aelurostrongylosis are not specific unless larvae are observed and overlap with those of other feline airway diseases.